(untitled) (Hematology Meeting Reports, 2009)
In patients undergoing high dose chemotherapy and hematopoietic stem cell transplant, oral mucositis (OM) is one of the most debilitating and annoying side effects. This complication results from cytotoxic injury to the epithelial lining of the oropharyngeal mucosa, although lesions of the whole gastrointestinal tract also occur.1 The severity of OM varies from erythema and edema accompanied by mild soreness to full mucosal thickness ulcerations penetrating into the submucosa, often resulting in severe pain requiring narcotic analgesia and impaired swallowing, prolonged hospitalization, and increased risks for infections and potentially life-threatening sequelae.2,3 Between 40% to 80% of cancer patients undergoing intensive treatment regimens requiring hematopoietic stem cell transplantation (HSCT) suffer the debilitating effects of OM during their cancer therapy.4,7